Effect of variation of load on swimmer's BLA and HR after exercise - Chen, W.; Gan, Q.; Yao, J. (Pre-olympic Congress 2004. Thessaloniki, Grécia. de 6 a 11 de Agosto de 2004, 2004)
The purpose of this study is to explore swimmer's reaction with different workload, which is important to improve the scientific design of load and reasonable monitoring in training program. Conclusions 1) BLA and HR showed different characteristics when varying distances and loads after loading, which provided advices for coaches to monitor load intensity and design loading program. 2) BLA should be taken into consideration in interval training besides HR.